The effect of rabeprazole alone or in combination with H2 receptor blocker on intragastric pH: A pilot study - Murat TÖRÜNER; Mehmet BEKTAŞ; Hülya ÇETİNKAYA and İrfan SOYKAN and Ali ÖZDEN (Turkish Journal of Gastroenterology, 2019)
-